Being Intentional about Antiracism in Social Work Supervision in England. - Tedam, Prospera; Cane, Tam (Social Work, 2026)
This article explores the importance of fostering intentional antiracism in social work supervision, emphasizing the need for supervisors to address and challenge racism within the supervisory process. As members of a profession rooted in social justice, supervisors must confront systemic inequalities, particularly racial inequities that affect service delivery, student learning, and workforce dynamics. Supervision is critical in shaping values, perspectives, and practices, making it an ideal space to cultivate antiracist frameworks. Intentional antiracism in supervision requires a proactive approach, where supervisors address individual and structural racism within current and historical contexts. Open dialogues about race, power, and privilege can help social workers develop the cultural sensitivity and self-awareness necessary to combat racial injustice in their own practice with individuals, families, and communities, as well as in their decision making. The article also highlights existing frameworks for integrating antiracist principles into supervision reflective practice, continuous professional development, and the use of antioppressive models. Through these efforts, social work supervision can serve as a transformative process, equipping practitioners to engage in culturally responsive, equitable, and just practices that better serve diverse populations. Ultimately, the authors endorse intentional antiracism in supervision using skilled dialogue to promote accountability, inclusivity, and ethical practice in the profession.